Amendment of municipal sewage sludge with lime and mussel shell: Effects on fate of organic matter and pharmaceutically active compounds. (15th February 2019) - Wang, Kun; Larkin, Tam; Singhal, Naresh; Zhuang, Tao
Graphical abstract: Highlight: Both additives stabilized municipal sewage sludge (MSS) organic decomposition. Organic functionality, composition and structure were modified after amendment. Lime increased available fractions of pharmaceutically active compounds (PhACs). Lime and mussel shell addition reduced PhACs' available fractions. Mixture of lime and mussel shell is recommended for amending MSS. Abstract: The deterioration in its strength from long-term degradation of organic matter and release of pharmaceutically active compounds (PhACs) have caused adverse environmental effects in municipal sewage sludge (MSS) landfill. Lime and a mixture of lime and mussel shell were employed as potential stabilization agents for MSS in this work. Their efficacy was assessed by investigating the effects on transformation of organic matter, as well as the occurrence and fate of four PhACs (fluoxetine, gemfibrozil, triclosan and carbamazepine) over 42 days. The addition of the selected agents: (i) prevented the microbial degradation of organic matter; (ii) modified the predominant functional groups of amide groups (amide I and II) and polysaccharides to deprotonated carboxylic groups and destruction of amide groups; and (iii) shifted the abundance of organic constituents from microbial by-products to humic acid-like organics with conformational changes. The measurement method provided reliable and precise results for determining PhAC concentrations in MSS with and without amendment, although matrix effects and process effects were found to affect measurement sensitivity. Available fractions of the PhACs increased in MSS with lime addition, but decreased in the presence of the mixture of lime and mussel shell due to the strong adsorption effects of the shells. The mixture of lime and mussel shell would be recommended for stabilizing MSS prior to being landfilled. However, longer term and larger scale investigation may be needed to better evaluate the applicability of lime and mussel shell for reducing the hazards and facilitating the management of MSS.